(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
This research aimed to identify, categorize, and assess Skinner’s declarations on science over six decades of the author’s intellectual production (1930 to 1980), in order to describe changes in Skinner’s positions on the subject. The investigation was based on the debate concerning contexts of discovery and justification and the pragmatics of science, embodied in this article in discussions regarding the internal logic of science and the scientific practice. Skinner maintains some of his positions on science over the decades, such as the adoption of the inductive method and critiques of deductivist hypotheses. However, a series of changes in Skinner’s discourse on the subject were identified, which goes from an initial emphasis on the internal logic of science to discussions more focused on scientific practice. This movement aligns Skinner more closely with the pragmatics of scientific investigation and a naturalistic epistemological trend.